Clinical significance of platelet count in infantile atopic dermatitis. - Gürkan, A.; Zorlu, P.; Şenel, S. (European Journal of Pediatric Dermatology, 2016)
Atopic dermatitis (AD) is a chronic inflammatory disease of the skin characterized by intense pruritus. Platelet count plays an important role in inflammatory processes of allergic diseases including AD. This study was aimed at determining the relation of platelet count to disease severity and laboratory values in infantile atopic dermatitis. In total, 112 infants with atopic dermatitis and 90 healthy controls were included in the study. The median platelet count was 423.5 × 103/μL in the patient group; this figure was significantly higher than in the control group (p<0,001). The platelet count did not significantly correlate with the objective SCORAD index (r=0.003, p=0.976), and there were no significant correlations between the total IgE levels and platelet counts in the patient group (r=-0.112, p=0.240). The platelet count significantly correlated with eosinophil count (p=0.009). Platelet count is elevated in early disease independently from the disease severity in infants suffering from atopic dermatitis.